2022
DOI: 10.1038/s41467-022-30116-x
|View full text |Cite
|
Sign up to set email alerts
|

Cofilactin filaments regulate filopodial structure and dynamics in neuronal growth cones

Abstract: Cofilin is best known for its ability to sever actin filaments and facilitate cytoskeletal recycling inside of cells, but at higher concentrations in vitro, cofilin stabilizes a more flexible, hyper-twisted state of actin known as “cofilactin”. While this filament state is well studied, a structural role for cofilactin in dynamic cellular processes has not been observed. With a combination of cryo-electron tomography and fluorescence imaging in neuronal growth cones, we observe that filopodial actin filaments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…2D projection images were lowpass-filtered using mtffilter in IMOD. Segmentations were generated in Dragonfly (Object Research Systems, 2022; www.theobjects.com/dragonfly ) as described previously 107 . In brief, isonet-filtered tomograms were further processed by histogram equalization and an unsharp filter, and a 5-class U-Net (with 2.5D input of 5 slices) was trained on 5–6 tomogram slices to recognize background voxels, filaments, membranes, cell surface structures and ribosomes.…”
Section: Methodsmentioning
confidence: 99%
“…2D projection images were lowpass-filtered using mtffilter in IMOD. Segmentations were generated in Dragonfly (Object Research Systems, 2022; www.theobjects.com/dragonfly ) as described previously 107 . In brief, isonet-filtered tomograms were further processed by histogram equalization and an unsharp filter, and a 5-class U-Net (with 2.5D input of 5 slices) was trained on 5–6 tomogram slices to recognize background voxels, filaments, membranes, cell surface structures and ribosomes.…”
Section: Methodsmentioning
confidence: 99%
“…It is activated both by cellular stresses, such as energy depletion (Nishida et al, 1987;Meberg et al, 1998;Minamide et al, 2000), and by signaling pathways, particularly those found at the leading edge of the cell (Arber et al, 1998;Meberg et al, 1998;Yang et al, 1998;Chan et al, 2000;Zebda et al, 2000;Endo et al, 2003). Indeed, filaments resembling cofilactin have been observed in the cytoplasm of neuronal growth cones in two recent cryoET studies (Atherton et al, 2022;Hylton et al, 2022). It remains to be seen whether cofilactin can also accumulate in the microtubule lumen during cell migration.…”
Section: Luminal Filaments Have Altered Morphology In Cofilin Knock-d...mentioning
confidence: 99%
“…Nat Commun. 13(1):2439. doi: 10.1038/s41467-022-30116-x 59 . ( C ) in vitro polymerized F-actin co-incubated with no protein, Drosophila Septins, human Septins, or Fascin.…”
Section: Introductionmentioning
confidence: 99%
“…However, saturated cofilactin filaments are no longer severed cofilin-dependently and are more flexible 50 , 52 , 58 . While examining actin bundles within filopodia at neuronal growth cones using cryo-electron tomography, Hylton and colleagues recently showed that cofilactin filaments associate with curvature of the actin bundles, thereby regulating filopodia structure and dynamics 59 . Interestingly, this cofilactin filament conformational change results in an exclusion of the Fascin actin-crosslinking protein from cofilactin bundles, leading to less organized actin filament bundling, the bending of filopodial protrusions, and a disruption of filopodial structure and functions ( Figure 2B ) 59 .…”
Section: Introductionmentioning
confidence: 99%